2008
DOI: 10.1007/s11276-008-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing delay-constrained throughput in multi-channel DS-CDMA ALOHA networks through power diversity and successive decoding

Abstract: We study multi-channel ALOHA networks (e.g., satellite-based networks) for online transaction processing, striving to maximize attainable throughput while meeting a deadline with near certainty. This captures the service provider's fixed costs and per-transaction revenue, the user's delay consciousness and ALOHA's probabilistic nature. Specifically, we consider CDMA channels and successive-decoding receivers. Interestingly, judicious use of power diversity is shown to be extremely effective: with a single tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The work of [14] was motivated by the observation that more sophisticated receivers that employ successive decoding can mitigate the problem caused by power diversity in con junction with CDMA. Indeed, it is shown that power diversity, in conjunction with optimized power levels and selection probabilities, can yield a significant throughput increase.…”
Section: E Power Diversity With Cdma and Sic Receiversmentioning
confidence: 99%
See 4 more Smart Citations
“…The work of [14] was motivated by the observation that more sophisticated receivers that employ successive decoding can mitigate the problem caused by power diversity in con junction with CDMA. Indeed, it is shown that power diversity, in conjunction with optimized power levels and selection probabilities, can yield a significant throughput increase.…”
Section: E Power Diversity With Cdma and Sic Receiversmentioning
confidence: 99%
“…Additionally, frequency-hopped CDMA (FH-CDMA) has been shown to have near-far resistance even with a single-user receiver [16]. As in [15], [14] embarks from the basic CDMA K-user channel model consisting of the sum of antipodally modulated signature sequences embedded in additive white Gaussian noise.…”
Section: E Power Diversity With Cdma and Sic Receiversmentioning
confidence: 99%
See 3 more Smart Citations